2018
DOI: 10.1534/g3.118.300578
|View full text |Cite|
|
Sign up to set email alerts
|

Defects in the Neuroendocrine Axis Contribute to Global Development Delay in a Drosophila Model of NGLY1 Deficiency

Abstract: N-glycanase 1 (NGLY1) Deficiency is a rare monogenic multi-system disorder first described in 2014. NGLY1 is evolutionarily conserved in model organisms. Here we conducted a natural history study and chemical-modifier screen on the Drosophila melanogaster NGLY1 homolog, Pngl. We generated a new fly model of NGLY1 Deficiency, engineered with a nonsense mutation in Pngl at codon 420 that results in a truncation of the C-terminal carbohydrate-binding PAW domain. Homozygous mutant animals exhibit global developmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 25 publications
7
34
0
Order By: Relevance
“…3B). 20 compounds had Z-scores greater than five in all three replicates ( Figure 3A), resulting in a suppressor hit rate of 0.781%, which is consistent with the hit rates we observed in previous whole-organism phenotypic drug repurposing screens in flies (Rodriguez et al, 2018) and yeast (Lao et al, 2019).…”
Section: As Shown Insupporting
confidence: 89%
“…3B). 20 compounds had Z-scores greater than five in all three replicates ( Figure 3A), resulting in a suppressor hit rate of 0.781%, which is consistent with the hit rates we observed in previous whole-organism phenotypic drug repurposing screens in flies (Rodriguez et al, 2018) and yeast (Lao et al, 2019).…”
Section: As Shown Insupporting
confidence: 89%
“…SKN-1A controls both basal and induced proteasome subunit gene expression and proteasome activity in C. elegans. The orthologs of PNG-1 and SKN-1A in Drosophila, mice, and human cells also control basal and induced proteasome subunit gene expression (Grimberg et al, 2011;Lee et al, 2011Lee et al, , 2013Owings et al, 2018;Radhakrishnan et al, 2010;Rodriguez et al, 2018;Steffen et al, 2010;Tomlin et al, 2017), indicating that deglycosylation of SKN-1A/Nrf1 is a conserved requirement for regulation of proteasome function in animals.…”
Section: Png-1/ngly1 and Skn-1a/nrf1 Control Proteostasismentioning
confidence: 99%
“…In an effort to phenotype and screen a homozygous loss-of-function Pngl / NGLY1 fly modeling the patient-derived C-terminal premature stop codon allele R401X, we showed that fly Pngl −/− homozygous mutant larvae are 25-fold more sensitive than heterozygotes to the toxic effects of bortezomib (Rodriguez et al, 2018). Another group reported that a Pngl RNAi-knockdown fly model of NGLY1 deficiency has constitutively reduced expression of NRF1-dependent proteasomal subunit genes, consistent with findings of hypersensitivity to bortezomib toxicity in the other models (Owings et al, 2018).…”
Section: Introductionmentioning
confidence: 99%